Pengelolaan stakeholder internal dan external dalam organisasi - Jumelda, Jumelda; Anantiasari, Amanda; Nurmala,; Agdiviyn Imanudin, Viola; Lidyanibras, Indah Firda Lidyanibra; Gariana, Muhamad Argi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article aims to analyze the strategy of managing internal and external stakeholders in an organization to improve operational effectiveness and achieve long-term goals. In the context of an organization, internal stakeholders consist of employees, management, and shareholders, while external stakeholders include customers, suppliers, communities, and regulators. Effective management of these two groups is expected to create synergy that supports the growth and sustainability of the organization. The methods used in this study include surveys and in-depth interviews with stakeholder representatives from various levels. The results of the study indicate that open communication, involvement in the decision-making process, and responsiveness to stakeholder needs and expectations are the keys to success in this relationship. In addition, this article also recommends a strategic approach through the use of information technology to improve interaction and collaboration with stakeholders. The conclusion drawn is that holistic stakeholder management can optimize organizational performance and increase the satisfaction of various parties involved.